Comparative Study of Carcass Characteristics and Meat Quality of Local Mediterranean Donkey Breeds - Mohamed Aroua; Hayet Haj Koubaier; Chaima Rekik; Antonella Fatica; Samia Ben Said; Atef Malek; Mokhtar Mahouachi; Elisabetta Salimei (Foods, 2024)
This study aimed to evaluate carcass and meat quality traits in Masri (n = 14) and North African (n = 14) male donkeys, raised in a semi-intensive breeding system, grazing on mountainous areas, with supplementation of 1 kg of barley per day per animal, slaughtered at 5 (±0.48) years old. Compared to Masri, the North African population exhibited higher (p < 0.05) final body weights (181.7 ± 2.1 and 212.5 ± 7.6 kg) and cold carcass weights (101.7 ± 1.3 and 116.2 ± 4.5 kg), but lower (p < 0.05) cold dressing percentages (56.0 ± 0.4 and 54.6 ± 0.4%). Meat quality analyses showed higher (p < 0.05) cooking loss values in Masri meat (43.9 ± 0.8 vs. 39.9 ± 1.2%). Among the meat color parameters, the hue value was higher (p < 0.05) in North African samples (0.42 ± 0.01 vs. 0.39 ± 0.1). Meat from North African donkeys had higher (p < 0.05) dry matter, fat, and protein contents. Meat amino acid analysis revealed abundant levels of lysine, leucine, and methionine, in both populations. Donkey meat from both populations presented a high polyunsaturated fatty acids content, resulting in polyunsaturated fatty acids/saturated fatty acids and omega 6/omega 3 ratios for all breeds close to the recommended values for human health. Atherogenic and thrombogenic indices were also suggested to have positive effects on consumers’ artery health. The characteristics of donkey meat present intriguing nutritional aspects compared to ruminant meat, and its production should be encouraged in the rural development of inner-Mediterranean areas.